Musa species in mainland Southeast Asia: From wild to domesticate - Christophe, Jenny; Gabriel, Sachter-Smith; Breton, Catherine; Ronan, Rivallan; Jean-Pierre, Jacquemoud-Collet; Cécile, Dubois; Matthieu, Chabannes; Ngoc-Sam, Ly; Thomas, Haevermans; Tien-Dung, Trieu; Oudomphone, Insisiengmay; Tin, Zhang; et al. (2024)
Many species are defined in the Musa section within its natural diversification area in Southeast Asia. However, their actual number remains debated as botanical characterisation, distribution and intraspecific variability are still poorly known, compromising their preservation and their exploitation as crop wild relatives of cultivated forms. To address the underexplored Musa diversity in mainland Southeast Asia, at the northern edge of the natural range, 208 specimens were collected in Vietnam, Laos and China, mainly belonging to Musa balbisiana, M. itinerans, M. acuminata and M. yunnanensis. Data on location, morphology, environment and local knowledge were recorded, and leaf samples collected for high-throughput genotyping. This study combines geographical, morphological, and genomic diversity to clarify the taxonomic classification. The collected species exhibit highly distinctive morphologies and genomes, just as they differ in ranges and life traits. Intraspecific genomic diversity was also observed, although not necessarily morphologically perceptible. Mainland Southeast Asia is confirmed as a primary diversification centre for the Musa section. The diversity observed is only partially represented in major international ex situ collections, calling for their urgent enrichment and the promotion of in situ management procedures, for the protection of these threatened species and to better harness their potential in breeding programmes. Although considered wild, the species studied are all affected to varying extents by human use. Musa yunnanensis and M. acuminata subsp. burmannica are the most strictly wild forms, with spontaneous interspecific hybrids first described in this study. Although gathered as fodder, they were only occasionally dispersed outside their endemic zones. Musa itinerans is not cultivated per se, but natural populations are widely exploited, leading to a geographically structured diversity. The diversity of M. balbisiana is widely distributed and geographically structured by human activities. This species should be regarded as domesticated. These various stages, from simple opportunistic gathering to true domestication, shed light on the evolutionary history of today’s cultivated varieties.